Barriers and Facilitators to Accessibility of Mental Health Services for Indigenous Youth in Canada: A Scoping Review ... - Chan, Andrea; Iwanicha, Peyton; Wiken, Ginny; Kirouac, Christopher; Meherali, Salima (OSF Registries, 2025)
The aim of this scoping review project is to gather and share evidence on the barriers and facilitators to accessing mental healthcare services by Indigenous youth in Canada, with the goal of empowering stakeholders to build on identifiable strengths and encourage action to overcome obstacles. ...